EVALUASI KINERJA DAN PERENCANAAN TRAYEK ANGKUTAN KOTA DI KOTA DENPASAR - Surya Tapa, I Gede Fery; Kumara, I Nyoman Indra; Indrashwara, Decky Cipta (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2024)
There have been many changes in the use of city transportation in Denpasar City since the 1990s until now. Therefore an evaluation of the transportation performance, planning of route systems, and the transportation operational system is needed. Primary data is obtained from headway, interview, and on-board surveys—the calculation of BOK, routes system planning, and operational systems using the Department of Transportation method. The results of the analysis show that almost all routes are not following the standards, both operational performance and service quality. The results of the new route planning are Renon-Penatih with a route length of 19,2 km, circulation time of 63,7 minutes, and the number of vehicles as many as 13 units ; Renon-Ubung with a length of the route of 22 km, circulation time of 69,8 minutes and the number of cars as many as 46 units; Renon-Sanur with a length of the route of 14,3 km, circulation time of 45,6 minutes and the number of vehicles as many as 3units; Renon-Sanglah-Lapangan Kompyang Sujana with a length of route of 18 km, circulation time of 57,9 minutes and the number of cars as many as 31 units; Renon-Sesetan-Suwung with a route length of 17,4 km, circulation time of 56,3 minutes and the number of cars as many as 29 units and; Renon-Teuku Umar-Pedungan with a route length of 15,1 km, circulation time of 47,9 minutes and the number of cars as many as 39 units.